2021
DOI: 10.1088/1755-1315/934/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Bacillus toyonensis in Tofu Wastewater

Abstract: Bacillus toyonensis has been isolated in Dumai mangrove ecosystem of Riau Province. One of factors affecting the growth of the bacteria is growth substrate. Tofu wastewater is rich in nutrition which can be used as substrate for bacterial growth. This research aimed to observe the growth of B. toyonensis in different concentration of tofu wastewater. The bacteria was grown in tofu wastewater at concentrations 8%, 10% and 12% was supplemented with 0.1 g K2HPO4, 0.15 g KH2PO4, 0.15 g NaCl and 0.5 g vitamin B12 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Soy whey is rich in nutrients and can be used as a growth substrate for some microorganisms (7). Nursyirwani et al found that Bacillus toyonensis increased exponentially in a substrate containing 12% TWW within 24 h (8). Rusydi et al found that Cyanobacteria Nostocmuscorum grew well in TWW medium at a concentration of 40% (9).…”
Section: Introductionmentioning
confidence: 99%
“…Soy whey is rich in nutrients and can be used as a growth substrate for some microorganisms (7). Nursyirwani et al found that Bacillus toyonensis increased exponentially in a substrate containing 12% TWW within 24 h (8). Rusydi et al found that Cyanobacteria Nostocmuscorum grew well in TWW medium at a concentration of 40% (9).…”
Section: Introductionmentioning
confidence: 99%